Pengelolaan Keuangan Daerah: Sebuah Kajian Fenomenologi terhadap Defisit Anggaran Kabupaten Majene - Amirullah, Sufyan; Edy, Sri Amalia; Mus, Sari Fatimah (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2024)
The budget deficit is an economic challenge in various regions in the last few decades. This is due to the expansion of government activities so that the main part of the total demand is allocated to spending, but on the income side the government is lacking to cover its large expenditures. This research focuses on the phenomenon of deficits that occur in Majene Regency for the 2022 fiscal year using a phenomenological approach with the concepts of noesis and noema to express intentionality and uses five (5) main stages of data analysis according to Moustakas. The goal to be achieved is to examine more deeply related to financial management in the realization of the Regional Revenue and Expenditure Budget (APBD) which is the cause of the deficit. The results of the study indicate that the main cause of the deficit is the failure to achieve the local revenue target and the program of activities has been running for a while, then efforts have been made to overcome and prevent the deficit, namely issuing circulars regarding the implementation of activity programs, conducting budget rationalization and evaluation of activity programs but also there are obstacles in its implementation such as changes in central government policies, the 2023 APBD contains political elements and there is no PERDA Accountability.